Refinement of Mouse Protocols for the Study of Platelet Thromboembolic Responses In Vivo - Rauzi, Francesca; Smyth, Erica; Emerson, Michael (Thrombosis and Haemostasis, 2017)
Mouse models of thromboembolism are frequently used to investigate platelet function in vivo and, according to European Union (EU) legislation, must be conducted in the context of replacement, refinement and reduction. We have previously developed a refined real-time mouse model of thromboembolism as an alternative to models of thromboembolic mortality which inflict considerable pain and suffering. Real-time monitoring involves infusion of radiolabelled platelets into the circulation of anaesthetized mice, and platelet aggregation is measured as increases in platelet-associated counts in the pulmonary vasculature following injection of platelet agonists. This gives a definitive data set on the tissue localization and extent of platelet activation. We developed an additional, more simplistic alternative to mortality models based on blood microsampling which entails the measurement of circulating platelet counts following agonist stimulation. Blood microsamples were collected from the tail vein of anaesthetized mice at three different time points leading to a reduction in animal numbers. Platelet counts significantly dropped 1 minute after stimulation with collagen or thrombin and were restored over 10 minutes. These results correlate with those obtained via real-time monitoring and were confirmed by immunohistochemistry. Pre-treatment of mice with aspirin significantly inhibited the decrease in platelet counts following collagen. These data suggest that blood microsampling may be implemented as a simplistic refined alternative to mortality models of thromboembolism when specialized monitoring equipment, or use of radioactive isotopes for real-time monitoring, which remains the ‘gold standard’, is not feasible. Microsampling refines and reduces animal procedures in compliance with current EU legislation.
Keywords: mouse model; platelets; thromboembolism